2015
DOI: 10.1016/j.cpr.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between pain and alcohol: An integrative review

Abstract: Pain and alcohol use are both highly prevalent in the general population, and pain-alcohol interrelations are of increasing empirical interest. Previous research has identified associations between pain and alcohol dependence, and the current review provides novel contributions to this emerging domain by incorporating studies that have tested relations between pain and low-to-moderate alcohol consumption, and by identifying potential psychosocial mechanisms of action. Specifically, we sought to integrate evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
162
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(188 citation statements)
references
References 142 publications
15
162
3
8
Order By: Relevance
“…A previous study reported a curvilinear association between alcohol consumption and pain 20 . Moderate alcohol consumption was associated with positive pain-related outcomes, such as higher QOL, whereas excessive consumption was associated with negative pain-related outcomes, such as higher pain severity 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported a curvilinear association between alcohol consumption and pain 20 . Moderate alcohol consumption was associated with positive pain-related outcomes, such as higher QOL, whereas excessive consumption was associated with negative pain-related outcomes, such as higher pain severity 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported a curvilinear association between alcohol consumption and pain 20 . Moderate alcohol consumption was associated with positive pain-related outcomes, such as higher QOL, whereas excessive consumption was associated with negative pain-related outcomes, such as higher pain severity 20 . Another study showed that alcohol dependence and chronic pain share common neural circuits; therefore, pain sensitivity and alcohol use may exert reciprocal effects 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Respondents reporting pain were handed cards that listed 31 bodily regions and were asked to identify to NHANES interviewers all regions where they experienced pain. Using the same criteria from a previous NHANES pain investigation, [12] we organized the 31 lateral pain region responses into the following seven pain locations: [1] back pain, [2] legs/feet pain, [3] arms/hands pain, [4] headache/migraine pain, [5] abdominal pain, [6] face/teeth pain, and [7] chest pain. These seven pain locations were coded as binary variables (1= present, 0 = not present) for analyses.…”
Section: Methodsmentioning
confidence: 99%
“…[4,5] Studies have found that, relative to pain-free individuals, those with chronic pain have higher rates of cigarette [5,6] and alcohol [7] use. The relationship between cocaine and other street drug use in the management of pain is less clear and has received less attention in the literature.…”
Section: Introductionmentioning
confidence: 99%